Audit partner, audit committee and audit report timeless in Oman: moderating effect of culture and family ownership - Raweh, Nahla Abdulrahman Mohammed (2020)
Audit report timeliness (ART) is a key determinant of timely financial reporting. It reflects the quality of accounting information and audit efficiency. Considering all the factors that can influence ART, this study empirically investigates some factors that influence ART in Oman. Specifically, the study examines the direct influence of culture, audit partner quality characteristics, and audit committee on ART. It also explores the moderating effect of both culture and family ownership on the relationship between audit committee characteristics and ART. Based on a sample of 327 firm-year observations from non-financial companies listed on the Muscat Securities Market for the period of 2013 to 2017, and applying a panel data analysis approach, this study reveals that culture (proxied by the proportion of tribal directors on the board), audit partner education and audit committee size prolong the production of audit reports. The study also finds that audit committee financial and industry expertise reduce the time taken to produce audit reports. Regarding the moderating effects, culture weakens the performance of audit committee size, independence, frequency of meetings and audit committee score and increases the time of audit reporting. This implies that culture hinders the effectiveness of audit committee mechanisms in promoting ART. In contrast, this study finds that the relationships of audit committee size, meeting and audit committee score with ART are strengthened by family ownership. This suggests that family ownership enhances the monitoring role of audit committee mechanisms and improves the speed of annual reporting, while the interaction of family ownership on audit committee independence weakens the independent directors from active monitoring, leading to longer audit report delay. The findings of this study may assist governance mechanisms and audit procedures, thus improving ART.